Should the Government Provide Unemployment Insurance to The Poor and Low-Income in Islamic Economics Perspective - Anniza Citra Prajasari (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
Poverty alleviation and unemployment reduction have been two missions that every country has to realize. This paper will examine other viewpoints in reviewing Unemployment Insurance (UI) policy for the poor and low-income people. In this regard, the role of government is crucial to determine a viewpoint that should be used for UI implementation for the poor. Does it need to involve the poor using unemployment or poverty context? If one uses the poverty context, do the poor and low-income need to be granted unemployment insurances? To answer those questions, this study conducted by utilizing a library review method, especially focusing on unemployment and UI in the Islamics perspective, and also the role of the state in realizing social security for the poor according to the Islamic Economists. This paper intends to argue that the government should not have to provide UI for the poor and low-income. That is because the poor, whether they are employed or not, have ‘economically poor’. So, the government’s main focus should not be on how to provide UI to the poor and low-income because they are unemployed but focus on how to alleviate poverty and improve their living standard through a more appropriate allowance, which is an effective poverty allowance. Keywords: unemployment insurance, unemployment in Islam, poverty allowance